Do precário ao plural: realidades e possibilidades da economia popular no Brasil contemporâneo - Sibelle Cornelio Diniz (2016)
This thesis discusses popular economy in Brazil, two decades after these formulations gained space in international debates. The main argument of this thesis is that the conditions for a strengthening of the popular economy across the public sector economy and enterprises economy are more favorable today than they were in the 1990s. It occurs due to three major movements that bring together central and peripheral countries around the debate of different modes of production: i) increasing articulation of the popular economy to the global production chains; ii) politicization that occurs with the urbanization throughout the territory; iii) growing criticism of the direction of the market society and the advancement of counter-movements in response. However, the rise of popular economy, from a precarious component of global networks to a key for a plural economy will not happen without major changes in the modes of regulation governing the daily relationships and the guidelines of public policies. The thesis puts notes for a debate in this direction, by discussing the recent advancement of popular and solidarity economy in Brazil and proposing to treat the Brazilian economy as an instituted plural economy: an economy that is characterized by the coexistence of economic principles, which complement each other in varying degrees, and is not autonomous from the social, but is, on the contrary, subject to the rules and laws established in each society, that is, an economic system that is, a priori, a socio-political construction.